Spatiotemporal distribution patterns of the two ecotypes of Coilia nasus in the middle-lower Yangtze River, China - Hu, Pengcheng; Yang, Zilai; Yang, Min; Sheng, Piao; Huang, Zhongyuan; Liu, Shuai; Chen, Yushun; Cao, Hong; Gao, Xin (Frontiers in Marine Science, 2025)
IntroductionDifferent ecotypes exhibit distinct life histories and occupy various environmental conditions for local adaptation. Coilia nasus, an anadromous fish, resides in offshore waters of the Pacific Northwest and reproduces in connected rivers and lakes, including the middle-lower Yangtze River. Populations of C. nasus have differentiated into two ecotypes: migratory and landlocked.MethodsThis study examined the spatiotemporal distributions of these ecotypes and the environmental conditions of their habitats by analyzing environmental DNA collected from Poyang Lake and Tai Lake during 2020–2021.ResultsA total of 157 eDNA samples were obtained, with 62 yielding positive results, including 23 from Poyang Lake and 39 from Tai Lake. The migratory population exhibited seasonal movements in Poyang Lake, entering the Yangtze River-Poyang Lake channel in spring, migrating southward during summer, and returning to the channel in autumn. In contrast, the spatial distribution of the landlocked population remained relatively stable throughout the seasons. Partial least squares structural equation modeling (PLS-SEM) analysis indicated that the distribution patterns of the migratory population were not significantly associated with environmental factors. In contrast, the distribution of the landlocked population was significantly affected by lower water turbidity and reduced conductivity.DiscussionThe findings suggest that temporal variations in the spatial distribution of C. nasus in Poyang Lake primarily reflect its migratory reproductive life history. Conversely, the distribution of the landlocked C. nasus population resembles that of resident fish populations and is mainly influenced by a preference for higher water quality. The results imply that differences in life histories and adaptation to local environmental conditions may have contributed to the formation of the two ecotypes. This study also shows the effectiveness of eDNA technology in assessing fish population distribution and dynamics.